Pengelolaan Kurikulum Merdeka Melalui Proyek P5: Studi Kasus Tema Suara Demokrasi di Sekolah Menengah Atas - Sirajuddin; Rugaiyah; Masduki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the management strategy of the Independent Curriculum through the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of Voice of Democracy at the Senior High School level. The study was conducted using a qualitative approach through a case study method, with data collection techniques in the form of in-depth interviews, direct observation, and document analysis related to project implementation. The findings show that the success of the project is highly dependent on collaborative planning between teachers and students, participatory implementation of activities, and evaluation based on critical reflection on the learning process and outcomes. The implementation of this project has a positive impact on strengthening students' character, especially in forming attitudes as active citizens, critical thinkers, and responsible in social and democratic life.